Natural CD8+CD122+ T Cells Are More Potent in Suppression of Allograft Rejection Than CD4+CD25+ Regulatory T Cells. Issue 1 (12th November 2013) - Dai, Z.; Zhang, S.; Xie, Q.; Wu, S.; Su, J.; Li, S.; Xu, Y.; Li, X. C.
<x xml:space="preserve">Abstract</x> Despite extensive studies on CD4+CD25+ regulatory T cells (Tregs), their application in adoptive transfer therapies is still not optimal in immune‐competent wild‐type (WT) animal models. Therefore, it is compelling to search for more potent Tregs for potential clinical application. Mounting evidence has shown that naturally occurring CD8+CD122+ T cells are also Tregs. However, their suppression in allograft rejection, efficiency in suppression and underlying mechanisms remain unclear. Using a murine allotransplantation model, we reported here that CD8+CD122+ Tregs were actually more potent in suppression of allograft rejection and underwent more rapid homeostatic proliferation than their CD4+CD25+ counterparts. Moreover, they produced more IL‐10 and were more potent in suppressing T cell proliferation in vitro. Deficiency in IL‐10 in CD4+CD25+ and CD8+CD122+ Tregs resulted in their reduced but equal suppression in vivo and in vitro, suggesting that IL‐10 is responsible for more effective suppression by CD8+CD122+ than CD4+CD25+ Tregs. Importantly, transfer of CD8+CD122+ Tregs together with the administration of recombinant IL‐15 significantly prolonged allograft survival in WT mice. Thus, for the first time, we demonstrate that naturally arising CD8+CD122+ Tregs not only inhibit allograft rejection but also exert this suppression more potently than their CD4+CD25+ counterparts. This novel finding may have important implications for tolerance induction.